Valuation of Czech bonds - Kompanová, Eliška; Málek, Jiří, 1953-; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This diploma thesis describes the process of valuation of Czech bonds. Its main contribution is the practical view on the matter, not the academic one. The knowledge is drew from our own professional experience and overview of Czech market. The thesis should serve as a comprehensive material for people who never really valuated any bond outside the academic field. Basic approaches and current market standards are described in an easy-to-understand way. Firstly, we focus on some basic information about bonds that is needed for grasping the whole topic. We present various types of bonds, risks related to them and interest rates used for valuation. Secondly, discounting and projection curves are described in more details. We explain the adjustments to the curves that are necessary for obtaining the fair value of a bond. Lastly, we show various valuation techniques using real bonds.
Vedoucí práce: Jiří Málek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses